2021
DOI: 10.1038/s41419-021-04218-1
|View full text |Cite
|
Sign up to set email alerts
|

Endocytic protein intersectin1-S shuttles into nucleus to suppress the DNA replication in breast cancer

Abstract: Breast cancer is the most common type of cancer worldwide. However, the well-known molecular biomarkers are not enough to meet the needs of precision medicine. In search for novel targets in this regard, we reported ITSN1 (intersectin1) as one of the candidates through mRNA microarray analysis. In the present study, we reported that endocytic protein ITSN1-S exists not only in the cytoplasm but also in nuclei of breast cancer cells. ITSN1-S′ functional nuclear localization signal is within its residues 306–312… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…www.nature.com/scientificreports/ Moreover, the GO and KEGG enrichment analysis found that the DNA replication, glucose metabolic process, and glycolysis pathways were the most enriched in the pathways related to IL score. Studies have discovered that cancer is correlated with errors that occur during DNA replication 50 , and the inhibition of DNA replication is shown to be beneficial to improve the prognosis of BRCA 51 . Recent research has demonstrated the crucial role played by glucose metabolic process in the growth of TNBC 52 .…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports/ Moreover, the GO and KEGG enrichment analysis found that the DNA replication, glucose metabolic process, and glycolysis pathways were the most enriched in the pathways related to IL score. Studies have discovered that cancer is correlated with errors that occur during DNA replication 50 , and the inhibition of DNA replication is shown to be beneficial to improve the prognosis of BRCA 51 . Recent research has demonstrated the crucial role played by glucose metabolic process in the growth of TNBC 52 .…”
Section: Discussionmentioning
confidence: 99%